Th-symmetrical hexakisadducts of C60 with a densely packed π-donor shell can act as energy- or electron-transducing systems - Diekers, Michael; Luo, Chuping; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2002)
For the first time several T-symmetrical hexakisadducts of C bearing up to six electro- and photoactive o-phenylene diamine or 9,10-dialkoxyanthracene moieties were synthesized and subjected to photoinduced electron/energy-transfer studies. Both donors form a densely packed π-donor shell surrounding the fullerene core. In these novel core-shell ensembles (7 and 19), either an efficient energy transfer from the dialkoxyanthracene periphery, or an electron transfer from the o-phenylene diamine periphery transduces the flow of excited-state energy or electrons, respectively, to the fullerene moiety, which resides in the central core. Due to the relatively high reduction potential of the fullerene core, which is anodically shifted by ≈0.7 V, compared with that of pristine C, the outcome of these intramolecular reactions depends mainly on the donor ability of the peripheral system. Interestingly, the charge-separated state in the o-phenylene diamine heptad (7; τ = 2380 ns in benzonitrile) is stabilized by a factor of 20 relative to the corresponding o-phenylene diamine dyad (6; τ = 120 ns in benzonitrile), an effect that points unequivocally to the optimized storage of charges in this highly functionalized fullerene ensemble.